2006
DOI: 10.1007/s10038-006-0408-3
|View full text |Cite
|
Sign up to set email alerts
|

Periaxin mutation in Japanese patients with Charcot-Marie-Tooth disease

Abstract: Periaxin (PRX) plays an important role in the myelination of the peripheral nerve and consequently in the pathogenesis of Charcot-Marie-Tooth disease (CMT). To date, nine nonsense or frameshift PRX mutations have been reported in eight families with CMT. The patients with PRX mutations appeared to show characteristic clinical features with early onset but slow or no progression, a common result of mutations that lead to missing a C-terminal acidic domain. Here, we report a Japanese CMT patient with these chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 14 publications
1
23
2
Order By: Relevance
“…Because myelin is necessary for the conduction of high-frequency and high-velocity nerve impulses by saltatory conduction, its defects lead to severe neuropathy. In humans, nonsense mutations in periaxin cause an autosomal recessive form of CMT4F (Dejerin-Sottas disease), which is one of the severe hereditary motor and sensory neuropathies [31,32]. It was also reported that periaxin-knockout mice exhibit peripheral demyelination, mechanical allodynia, and thermal hyperalgesia [33].…”
Section: Resultsmentioning
confidence: 99%
“…Because myelin is necessary for the conduction of high-frequency and high-velocity nerve impulses by saltatory conduction, its defects lead to severe neuropathy. In humans, nonsense mutations in periaxin cause an autosomal recessive form of CMT4F (Dejerin-Sottas disease), which is one of the severe hereditary motor and sensory neuropathies [31,32]. It was also reported that periaxin-knockout mice exhibit peripheral demyelination, mechanical allodynia, and thermal hyperalgesia [33].…”
Section: Resultsmentioning
confidence: 99%
“…In order to identify putative protein ligands for the C-terminal segment of L-PRX, which is missing in the presence of the CMT4F R1070X mutation (24,28), we carried out a yeast 2-hybrid screen of a rat sciatic nerve cDNA library with the C-terminal segment, missing upon the R1070X mutation, as bait. As a result, we obtained three separate clones containing the β4-FNIII-3 domain (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…Proteomics analyses were carried out exactly as described (24), comparing the PRX-bound proteomes of PRX -/- mice carrying a transgene for either wild-type PRX (PrxTg/PRX -/- ) or PRX with a C-terminal truncation mutation (mouse L-PRX truncated at residue 1016; ΔCPrxTg/PRX -/- ) corresponding to human CMT4F R1070X (28,29). Proteins from mouse nerve lysates were crosslinked followed by immunoprecipitation with a PRX antibody, and then subjected to mass spectrometry (MS) analyses.…”
Section: Methodsmentioning
confidence: 99%
“…So far, 10 different frameshift or non‐sense PRX mutations were reported to cause autosomal recessive (AR) early‐onset demyelinating neuropathy [6]. It develops further in the course either as severe Dejerine–Sottas syndrome [7,8] or demyelinating CMT with slow or no progression [8–10].…”
Section: Introductionmentioning
confidence: 99%
“…The protein has four characteristic domains: PDZ, nuclear localization signal, repeat and acidic domains [13–15]. Loss of the acidic domain is shared by all pathogenic mutations in the gene reported so far and presumably plays a role in the disease pathogenesis [7–10,16].…”
Section: Introductionmentioning
confidence: 99%